Creating an Integrated Undergraduate Public Health Curricula: Inspiring the Next Generation to Solve Complex Public Health Issues - Osiecki, Kristin; Barnett, Jessie; Mejia, Angie (Frontiers in Public Health, 2022)
This article takes a novel approach of highlighting the creation and development of an integrated undergraduate public health curricula geared to students in the health sciences. In our practice, undergraduate and public health pedagogy supports innovative and proven approaches of experiential learning in our classrooms. We show how public health faculty take a team approach to teaching which has allowed them to collaborate in and outside of the classroom resulting in inherent knowledge of course materials, student engagement, and outcomes. This evolved to an overall curricula design that involves scaffolded research skills and/or projects within and between the public health courses. In addition, we highlight examples of upperclassmen utilizing these curriculum schemas outside the classroom to engage in faculty research beyond the public health discipline. This narrative describes lessons learned when teaching undergraduate students across public health curricula, how we integrated research skills within each course using pedagogical practices, and why this approach supports student engaged research within directed study and paid undergraduate research opportunities.